2018
DOI: 10.15520/ijcrr/2018/9/08/582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Culture and Organizational Commitment to Employee Performance through Organizational Citizenship Behavior (OCB) as Intervening Variables (Study on Bappeda Litbang Provinsi Bali)

Abstract: Organizational culture as the values, principles, traditions and ways of working shared by members of the organization and affect the way they act. Organizational commitment has an important role of employee performance. The commitment can be realized if the individual in the organization, running their rights and obligations according to their duties and functions and functions within the organization, because the achievement of organizational goals is the work of all members of the organization that are coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
4
13
1
10
Order By: Relevance
“…Ini mungkin terjadi karena kondisi OCB tergantung pada faktor-faktor lain yang terpengaruh. Secara teoritis dan empiris apa yang telah secara signifikan mempengaruhi OCB adalah komitmen organisasional (Hasani, Boroujerdi & Sheikhesmaeili, 2013;Irhas, 2017;Mihdar, 2013;Prasetio, Siregar & Luturlean, 2015;Serpian, et al, 2016;Shahmohammadi & Afzooni, 2018;Suwibawa, Agung & Sapta, 2018;Yazdani & Parsa, 2014).Meskipun beberapa hasil penelitian mendukung pengaruh antara komitmen organisasional terhadap OCB, terdapat beberapa penelitian yang tidak mendukung temuan tersebut. Pernyataan ini didukung oleh penelitian sebelumnya yang dilakukan Kartika, Kaihatu, Adiwijaya, dan Nugroho (2016) yang telah menyimpulkan bahwa komitmen organisasional berkorelasi terhadap OCB, tetapi tidak signifikan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Ini mungkin terjadi karena kondisi OCB tergantung pada faktor-faktor lain yang terpengaruh. Secara teoritis dan empiris apa yang telah secara signifikan mempengaruhi OCB adalah komitmen organisasional (Hasani, Boroujerdi & Sheikhesmaeili, 2013;Irhas, 2017;Mihdar, 2013;Prasetio, Siregar & Luturlean, 2015;Serpian, et al, 2016;Shahmohammadi & Afzooni, 2018;Suwibawa, Agung & Sapta, 2018;Yazdani & Parsa, 2014).Meskipun beberapa hasil penelitian mendukung pengaruh antara komitmen organisasional terhadap OCB, terdapat beberapa penelitian yang tidak mendukung temuan tersebut. Pernyataan ini didukung oleh penelitian sebelumnya yang dilakukan Kartika, Kaihatu, Adiwijaya, dan Nugroho (2016) yang telah menyimpulkan bahwa komitmen organisasional berkorelasi terhadap OCB, tetapi tidak signifikan.…”
Section: Pendahuluanunclassified
“…Efeknya positif di mana itu berarti bahwa semakin tinggi komitmen organisasional, semakin tinggi perilaku OCB. Sudut pandang penelitian yang mendukung hubungan antara komitmen organisasi dan OCB, seperti penelitian Hasani, Boroujerdi & Sheikhesmaeili (2013) ;Indarti, et al, (2017); Irhas (2017); Mihdar (2013); Prasetio, et al, (2015) ;Serpian, et al, (2016); Shahmohammadi & Afzooni (2018) ;Suwibawa, et al, (2018); Yazdani & Parsa (2014). Para peneliti terdahulu tersebut memiliki argumen yang sama tentang arah pengaruh yang positif dan signifikan antara variabel-variabel ini.…”
Section: Metode Penelitianunclassified
“…These indicators if developing in a good condition can be influences OCB. The results of the study which concluded that organizational commitment affects OCB, including among others conducted by Saxena dan Saxena (2015), Suwibawa et al (2018), Kusumaninggati et al (2018), and Shahjehan et al (2019). Based on the studies and statements, the third hypothesis in this study is: H3: Organizational commitment has a direct effect on OCB.…”
Section: Organizational Commitment and Ocbmentioning
confidence: 65%
“…A szervezeti kultúra típusa, erősségei és gyengeségei nagymértékben befolyásolják a vezetők és beosztottak magatartását, viselkedésbeli megnyilvánulásait és eredményességét (Atchison, 2002;Bakacsi, 2006;Karácsony, 2006;Ebrahimpour et al, 2011, Ujhelyi et al, 2016Gál et al, 2017), az uralkodó kultúra tehát kapcsolatban áll a munkavállalók által tanúsított szervezeti polgár magatartással (Kar-Tewari, 1999). A szervezeti kultúra és az OCB összefüggéseivel a közelmúltban számos kutató foglalkozott (Mohanty & Rath, 2012;Chun et al, 2013;Ghashghaeinia & Hafezi, 2015;Badwy et al, 2017;Suwibawa et al, 2018;Arumi et al, 2019).…”
Section: A Szervezeti Kultúra éS a Szervezeti Polgár Magatartás Kapcsunclassified
“…A tanulmányuk legfontosabb konklúziója szerint az erős szervezeti kultúra erős OCB-dimenziókat eredményez. Suwibawa et al (2018) A vonatkozó kutatások eredményei alapján indokoltnak tartottunk tehát összehasonlító vizsgálatokat végezni a köz-és versenyszféra munkavállalóinak körében az észlelt szervezeti kultúra és a szervezeti polgár magatartás közötti összefüggésekre vonatkozóan. A versenyszféra munkavállalóinak körében ugyanis egyértelműen kimutatták, hogy mind a négy kultúratípus kapcsolatban van az OCB-dimenziókkal, a közszféra dolgozóinak körében csupán egy vizsgálatról tudunk (Kim, 2014), ami kizárólag a klánkultúra vonatkozásában elemezte az összefüggést.…”
Section: A Szervezeti Kultúra éS a Szervezeti Polgár Magatartás Kapcsunclassified